2008
DOI: 10.4238/vol7-2gmr446
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between structural and biochemical characteristics and texture of corn grains

Abstract: AbStRACt. The texture of corn grains is a fundamental characteristic for the industry as well as for grain producers and processors. To further understand the mechanisms involved in grain hardness, contrasting corn cultivars for grain hardness and protein quality were evaluated. The cultivars were Cateto L 237/67 (hard endosperm and low protein value), QPM BR 451 (semi-hard endosperm and high protein value); Bolivia-2 (floury endosperm and low protein value), and Opaque-2 (floury endosperm and high protein val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 13 publications
(11 reference statements)
7
17
0
2
Order By: Relevance
“…It is known that MF industry prefers hard endosperm maize, as opposed to TM that favours white landraces [17]. Previous studies report PC, on dry basis, for MD tortillas of 7.58-15.63 g/100 g [10,[18][19][20][21].…”
Section: Chemical Composition Of Tortillas By Raw Materials and Point mentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that MF industry prefers hard endosperm maize, as opposed to TM that favours white landraces [17]. Previous studies report PC, on dry basis, for MD tortillas of 7.58-15.63 g/100 g [10,[18][19][20][21].…”
Section: Chemical Composition Of Tortillas By Raw Materials and Point mentioning
confidence: 99%
“…Previous studies report PC, on dry basis, for MD tortillas of 7.58-15.63 g/100 g [10,[18][19][20][21]. These reports have different maize descriptions, suggesting phenotypes were different; but also is known PC varies according to endosperm hardness [17]. However, on dry basis, results between MD and MF, were similar (p>0.05) and differences, per 100 g of fresh weight, are due to losses that take place during cooking, pericarp removal and wet milling of nixtamal in TM [5,21].…”
Section: Chemical Composition Of Tortillas By Raw Materials and Point mentioning
confidence: 99%
“…In the Table 5 Pereira et al (2008) reported that corn kernels with hard or dent endosperms have abundance of organized protein bodies what explain the compact of these endosperms. A positive correlation was observed between lipid content and kernel real density (r = 0.67, at 95 % of confidence).…”
Section: Correlation Analysismentioning
confidence: 99%
“…No se registraron diferencias estadísticas para contenido de triptófano sobre proteína total entre líneas endogámicas CIG tipo CP con endosperma harinoso y las que tienen granos con endosperma vítreo o modificado (±t Student = 1,9; n.s.). Los resultados presentados en la Tabla 4.26 también coinciden con datos de varios autores (Wallace et al, 1990;Lópes et al, 1995;Azevedo et al, 2003;Krivanek et al, 2007;Pereira et al, 2008) que señalaron que seleccionar materiales con alta calidad proteica y endosperma duro conlleva a una cierta reducción de la calidad proteica respecto del opaco-2 en su estado puro porque aumenta la proporción de las prolaminas α-zeína y, sobre todo, hasta 2 y 3 veces la γ-zeína, ambas determinantes de la mayor dureza del grano (Paiva et al, 1991; DombrinkKurtzman y Bietz, 1993) pero pobres en aminoácidos esenciales.…”
Section: Figura 438: Mesa De Luz Y Líneas Endogamicas Con Granos De unclassified
“…Pereira et al, 2008;Sánchez et al, 2007;Krivanek et al, 2007). El triptófano puede fluctuar desde 0,2% a 0,5% (media= 0,4%) para maíz normal o desde 0,5% a 1,9% (media= 0,8%) para maíz de alta calidad proteica (Moro et al, 1996;Balconi et al, 1998;Krivanek et al, 2007 Gevers (1975).…”
Section: Tabla 429 Comparación De Los Niveles De Aminoácidos Esenciaunclassified